2020
DOI: 10.3892/mmr.2020.11545
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response and oxidative stress attenuated by sulfiredoxin‑1 in neuron‑like cells depends on nuclear factor erythroid‑2‑related factor 2

Abstract: Sulfiredoxin-1 (SRX1) is a conserved endogenous antioxidative protein, which is involved in the response to cellular damage caused by oxidative stress. Oxidative stress and inflammation are the primary pathological changes in spinal cord injuries (SCI). The aim of present study was to explore the roles of SRX1 in SCI. Using reverse transcription-quantitative PCR and western blotting, the present study discovered that the expression levels of SRX1 were downregulated in the spinal cord tissues of SCI model rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Hyperuricemia is considered the primary pathogenic factor in the etiopathogenesis of gout arthritis, where the precipitation of MSU crystals in the lower limbs joints and cartilage causes synovitis and cartilage degeneration through stimulation of the innate immune receptor ( Braga et al, 2017 , Chen-Xu et al, 2019 ). Uric acid acts as a danger signal, resulting in a low grade of inflammation in gout and other metabolic disorders ( Wu et al, 2020 , Kushiyama et al, 2012 ). In response to innate immune danger e.g., uric acid in the joint microenvironment, synovial macrophages can be activated by urate crystals to enhance the secretion of IL-1β, recruit inflammatory monocytes, and shift the macrophages population into a pro-inflammatory phenotype which in turn drives the acute inflammatory response ( Liu et al, 2022 , Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperuricemia is considered the primary pathogenic factor in the etiopathogenesis of gout arthritis, where the precipitation of MSU crystals in the lower limbs joints and cartilage causes synovitis and cartilage degeneration through stimulation of the innate immune receptor ( Braga et al, 2017 , Chen-Xu et al, 2019 ). Uric acid acts as a danger signal, resulting in a low grade of inflammation in gout and other metabolic disorders ( Wu et al, 2020 , Kushiyama et al, 2012 ). In response to innate immune danger e.g., uric acid in the joint microenvironment, synovial macrophages can be activated by urate crystals to enhance the secretion of IL-1β, recruit inflammatory monocytes, and shift the macrophages population into a pro-inflammatory phenotype which in turn drives the acute inflammatory response ( Liu et al, 2022 , Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor (Nrf2) contributes significantly to cellular defense against oxidative insult via binding to the antioxidant response element (ARE). This binding enhances the expression of genes coding for antioxidant proteins, including HMOX1 and srxn1 ( He et al, 2020 ; Loboda et al, 2016 , Wu et al, 2020 ). Previous findings demonstrated that Zer inhibited reactive oxygen species (ROS) generation via upregulation of Nrf2 expression ( Wu et al, 2020 , Yang et al, 2018 ; Leung et al, 2017 ; Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, overexpression of Srx prevents many oxidative damages and apoptosis by modulating the activity of the stress response, inflammatory and apoptotic pathways [ 33 ]. In this way, Srx may confer a neuroprotective function [ 42 , 43 , 44 ] or rescue cardio tissues from injury [ 45 ] or play a role in kidney protection [ 46 ]. Srx is also essential for normal responses to receptor stimulation in endocrine system signaling [ 47 ].…”
Section: Discussionmentioning
confidence: 99%